Raman evolution of order–disorder phase transition in multiaxial molecular ferroelectric thin film. (1st July 2019) - Zafar, Zainab; Zafar, Amina; Guo, Xitao; Lin, Qian; Yu, Yuanfang
Abstract: Multiaxial molecular ferroelectrics (MFe) attain great attention due to their number of equivalent ferroelectric axes, an essential characteristic for many applications of these polar polycrystalline materials. Here we report a systematic approach to reveal the temperature‐dependent Raman spectroscopic investigation of the vibrational properties of a [Hdabco]ReO4 (dabco = 1, 4‐diazabicyclo[2.2.2]octane), a multiaxial MFe thin film. The Raman spectra allowed to obtain information relative to the change in molecular symmetry governed by the order–disorder phase transition. This phase transition is manifested by the temperature‐dependent peak shift, full width half maximum and intensity of distinct vibrational modes. The experimental observation reveals that ferroelectric phase transition is mainly driven by the reorientation motion of the ReO4 − anions and monopronated dabco cations. Hence, we demonstrated that the Raman spectroscopy is a very useful tool to characterize the newly emerged MFe system. Abstract : A systematic approach to reveal the temperature‐dependent Raman spectroscopic investigation of [Hdabco]ReO4 (dabco = 1, 4diazabicyclo[2.2.2]octane), a multiaxial molecular ferroelectrics thin film has been investigated. The Raman spectra allowed obtaining information relative to the change in molecular symmetry governed by the order–disorder phase transition. This symmetry change during the phase transition is associated with the manifestation of full width half maximum, wavenumber, and intensity of ν(ReO) mode at 961 cm −1 and ν(C‐N) mode at 802 cm −1 .